An improvement of the child acute respiratory infection treatment program - E. N. Simovan'yan; E. E. Badalyants; L. P. Sizyakina; A. A. Lebedenko; V. B. Denisenko; M. A. Kim (Педиатрическая фармакология)
High morbidity rate, frequent development of severe complication forms, unfavorable remote effects for children’s health, insufficient efficacy of the used acute respiratory infection therapy schemes necessitate a treatment program improvement for this group of diseases. A complex clinical-laboratory examination of 72 3-6-year-old children with acute nasopharyngites and bronchites was conducted. Dependence of the disease’s clinical form and course peculiarities from the premorbid setting state and immune status changes’ intensity has been found. It has been established that the introduction of inosine pranobex in the complex treatment of acute respiratory infections in children favors rapid positive dynamics of clinical symptomatology and immune status parameters and is not accompanied by the development of side effects. Thus, high efficacy and safety of inosine pranobex’s use allow to recommend introducing this drug into the treatment program for children of 3 years of age and older with acute respiratory infections regardless of the disease form and immune status state.